Long-Term Sonographical Follow-Up of Arterial Stenosis Due to Spontaneous Cervical Artery Dissection - Strunk, Daniel; Schwindt, Wolfram; Wiendl, Heinz; Dittrich, Ralf; Minnerup, Jens (Frontiers in Neurology, 2022)
Purpose Little is known about the long-term course of arterial stenosis after spontaneous cervical artery dissection (sCAD). We analyzed changes over time and evaluated factors potentially associated with these changes and recurring sCAD. Materials and Methods Adult patients with sCAD, admitted to our neurological department between 2004 and 2018 were included. All patients underwent initial and follow-up repetitive neurovascular ultrasound for a mean duration of 15,3 ± 21 months. Clinical and imaging data were registered in each patient. Results Two hundred fifty-nine sCAD were diagnosed in 224 patients. Either internal carotid arteries (n=133, 59.4%), vertebral arteries (n=58, 25.9%), or multiple arteries (n=33, 14.7%) were affected. In 183 patients 93 (51%), and of 210 arteries 117 (55.7%) degrees of stenosis improved over time. Occluded arteries recanalized early in 34 (54%) and stayed occluded in 29 patients (46.0%, p=0.74). Of 145 initially hemodynamically relevant stenoses 77 (53.1%) improved over time. Overall, 12 patients (5.4 %) had a recurring sCAD during follow-up. Pseudoaneurysms were found in 19 patients. Conclusion The sonographical course of sCAD is highly dynamic within the first year after disease onset and should be monitored carefully. Decreasing degrees of stenosis and recanalization of occluded arteries occurred in half of all patients. Recurrent sCAD was a rare event in our cohort.